NonClassic Congenital Adrenal Hyperplasia. (13th May 2010) - Witchel, Selma Feldman; Azziz, Ricardo
Abstract : Nonclassic congenital adrenal hyperplasia (NCAH) due to P450c21 (21-hydroxylase deficiency) is a common autosomal recessive disorder. This disorder is due to mutations in the CYP21A2 gene which is located at chromosome 6p21. The clinical features predominantly reflect androgen excess rather than adrenal insufficiency leading to an ascertainment bias favoring diagnosis in females. Treatment goals include normal linear growth velocity and "on-time" puberty in affected children. For adolescent and adult women, treatment goals include regularization of menses, prevention of progression of hirsutism, and fertility. This paper will review key aspects regarding pathophysiology, diagnosis, and treatment of NCAH.